FURTHER STUDIES ON ADOPTIVE TRANSFER OF SENSITIVITY TO SKIN HOMOGRAFTS - Billingham, R. E. (The Rockefeller University Press, 1963)
Mice or rats that have been rendered tolerant of skin homografts from an alien donor strain furnish the basis of a very sensitive and objective test system for investigating the competence of cellular inocula from specifically immunized isologous donors to transfer sensitivity adoptively. By means of this test system it has been shown that immunologically "activated" cells, capable of transferring homograft sensitivity, are present in the blood, peritoneal exudates, and regional nodes of animals that have rejected skin homografts. Leucocytes were as effective as regional node cells. Activated cells were first demonstrable in the regional nodes and blood of skin homograft recipients at the same time,—on the 6th postoperative day,—suggesting that these cells must enter the circulation very soon after their formation in the nodes. Moreover, when sensitization was effected by skin homografts, but not by means of splenic cell suspensions inoculated intraperitoneally, activated cells are highly persistent, still being demonstrable in both the blood and the nodes more than a year after sensitization. The finding that thoracic duct cells, which are almost exclusively lymphocytes, were just as effective as leucocytes or regional nodes in transferring sensitivity in rats formally identifies the cell type responsible for transferring sensitivity in the various tissues tested. Attempts to transfer sensitivity to homografts in normal mice or tolerant mice by means of larger dosages of activated lymphoid cells sequestered in Millipore chambers inserted intraperitoneally were unsuccessful. All this, and other evidence presented, lends strength to the thesis that skin homograft immunity is a cell-mediated reaction.